Regional ecological risk assessment for Guangxi (China) based on entropy method and the pressure-capital-vulnerability-response model - Hui Wang (Ecological Indicators)
Regional ecological risk assessment (RERA) is an important macroscopic environmental management tool and can provide specific approaches for ecological protection and sustainable development. In this research, through incorporating entropy method and pressure-capital-vulnerability-response (PCVR) model into RERA flowchart, the cause-effect-response relationship between human and environment was manifested within RERA context. Among the PCVR-RERA framework, production-living socioeconomic activities constitute human-caused ecological risk source pressures whereas land use ecology function forms the ecological risk receptor capital. Besides, circular economy (CE)-pertinent indexes were acquired for the characterization purpose of human response risk in coping with ecological issues and this CE-based human response risk manifestation scheme was an important improvement for RERA research. As for vulnerability, apart from slope, vegetation, soil and dryness factors, karst distribution index was also incorporated into the expression of final comprehensive eco-environmental vulnerability of Guangxi. The results of the study showed that: (1) the southeast part of Guangxi had higher human-caused ecological risk source pressure and lower integrated eco-environmental vulnerability, whereas the vast west and northeast parts had lower human-related ecological risk source pressure and higher comprehensive eco-environmental vulnerability. (2) Most developed cities within Guangxi, such as Liuzhou, Nanning, Guilin and Beihai, had lower human response risk whereas the less developed cities, like Baise, Chongzuo and Hechi, had higher human response risk, meaning that within developed cities, CE’s development was more satisfied. (3) Within Guangxi, the central and western parts had higher final ecological risk because of higher eco-environmental vulnerability and human response risk there. On the contrary, the Hezhou City had the lowest final ecological risk owing to its lower human production-living disturbance and eco-environmental vulnerability level. At last, this research made clear the foci of regional ecological risk management (RERM) for Guangxi, e.g., mitigating human response risk through reinforcing CE development with respect to natural resources’ reducing, reusing, and recycling, and enhancing karst ecological restoration to cope with anthropogenic and natural influences in western karst regions of Guangxi. All these RERM countermeasures will be helpful for the constructions of circular society and ecological civilization within Guangxi, China.